Integrated management: chronic kidney disease, diabetes mellitus, hypertension - Naicker, Sarala (African Journal of Nephrology, 2013)
<p style="margin: 4px; color: #000000; font-family: ’Merrieweather sans’, sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">The increasing burden of chronic kidney disease and end stage kidney failure presents a challenge for both developedand emerging countries. While dialysis and transplantation consumes an ever-increasing proportion of the health budgetin countries such as the United States, Japan and Taiwan, there is limited availability of these expensive therapies in themajority of emerging countries and more so in African nations. <p style="margin: 4px; color: #000000; font-family: ’Merrieweather sans’, sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Aims: To review the prevalence, causes and integrated strategies for treatment and prevention of end stage renaldisease (ESRD) in Sub-Saharan Africa (SSA). <p style="margin: 4px; color: #000000; font-family: ’Merrieweather sans’, sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Materials and Methods: Review of literature and information received from colleagues in Africa. <p style="margin: 4px; color: #000000; font-family: ’Merrieweather sans’, sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Results: Approximately 70% of the least developed countries of the world are in SSA. Rapid urbanisation is occurringin many parts of the continent, contributing to overcrowding and poverty. While infections and parasitic diseases arestill the leading cause of death in Africa, non-communicable diseases are coming to the forefront. There is a continuingbrain drain of healthcare workers (physicians and nurses) from Africa to more affluent regions, resulting in largerural areas of Africa having no health professionals to serve these populations. There are no nephrologists in manyparts of SSA; the numbers vary from 0.5 per million population (pmp) in Kenya to 0.6 pmp in Nigeria, 0.7 pmp inSudan and 1.1 pmp in South Africa. <p style="margin: 4px; color: #000000; font-family: ’Merrieweather sans’, sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Chronic kidney disease (CKD) affects mainly young adults aged 20-50 years in SSA and is primarily due to hypertensionand glomerular diseases. HIV-related chronic kidney disease is assuming increasing prominence and often presentslate, with patients requiring dialysis. Diabetes mellitus affects 9.4-million people in Africa. The prevalence of diabeticnephropathy is estimated to be 6-16% in SSA. The current dialysis treatment rate is <20pmp (and nil in many countriesof SSA), with in-centre haemodialysis the modality of renal replacement therapy (RRT) for the majority. Transplantationis carried out in a few SSA countries: South Africa, Sudan, Nigeria, Mauritius, Kenya, Ghana and Rwanda, with mostof the transplants being living donor transplants, except in South Africa where the majority are from deceased donors.Prevention programmes are in their infancy in most of SSA, due to lack of personnel and resources. <p style="margin: 4px; color: #000000; font-family: ’Merrieweather sans’, sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Conclusion: Chronic kidney disease care is especially challenging in SSA, with large numbers of ESRD patients,inadequate facilities and funding, and lack of national or regional registries. Integrated management of CKD and itsrisk factors is necessary to impact on the burden of ESRD.